2014
DOI: 10.1128/jvi.02572-13
|View full text |Cite
|
Sign up to set email alerts
|

Measles Virus C Protein Impairs Production of Defective Copyback Double-Stranded Viral RNA and Activation of Protein Kinase R

Abstract: Measles virus (MV) lacking expression of C protein (C KO ) is a potent activator of the double-stranded RNA (dsRNA)-dependent protein kinase (PKR), whereas the isogenic parental virus expressing C protein is not. Here, we demonstrate that significant amounts of dsRNA accumulate during C KO mutant infection but not following parental virus infection. dsRNA accumulated during late stages of infection and localized with virus replication sites containing N and P proteins. PKR autophosphorylation and stress granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
98
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 62 publications
6
98
0
Order By: Relevance
“…We earlier found that ADAR1 suppressed multiple dsRNA-dependent innate activities, including the activation of PKR, the IPS-dependent induction of IFN, and the formation of SG in cells infected with WT and V mutant measles virus (7,25,27). However, suppression of these dsRNA-dependent responses by ADAR1 remarkably was not observed with the measles C mutant (7,25,27), a mutant now understood to produce much higher amounts of viral dsRNA than either WT or the V mutant virus (23,27,64). Our results described herein, together with those of others (65)(66)(67), reveal that in the absence of ADAR1 at least some of the cytoplasmic sensors of dsRNA are also triggered by cellular (self) dsRNAs.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We earlier found that ADAR1 suppressed multiple dsRNA-dependent innate activities, including the activation of PKR, the IPS-dependent induction of IFN, and the formation of SG in cells infected with WT and V mutant measles virus (7,25,27). However, suppression of these dsRNA-dependent responses by ADAR1 remarkably was not observed with the measles C mutant (7,25,27), a mutant now understood to produce much higher amounts of viral dsRNA than either WT or the V mutant virus (23,27,64). Our results described herein, together with those of others (65)(66)(67), reveal that in the absence of ADAR1 at least some of the cytoplasmic sensors of dsRNA are also triggered by cellular (self) dsRNAs.…”
Section: Discussionmentioning
confidence: 93%
“…A simple explanation is that the suppression results from the destabilization of duplex RNAs, either cellular dsRNA regions as shown herein (Figs. 4 and 5) and also by Walkley and co-workers (65) or viral dsRNA structures as seen with the measles virus (23,64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein extracts of infected cells (MOI ϭ 0.1, 30 to 48 h postinfection) were generated, and protein concentrations were determined as described previously (14). Protein (25 g) was fractionated using 12% polyacrylamide gels and transferred to Immobilon-P membranes (EMD Millipore, Billerica, MA) using a semidry protocol.…”
mentioning
confidence: 99%
“…Infection of HeLa cells and immunostaining for dsRNA and MV N protein were performed as described previously (14). Slides were analyzed using an LSM 780 inverted laser scanning confocal microscope and ZEN 2012 (Black Edition, v8.0) software (Carl Zeiss Microscopy, Jena, Germany).…”
mentioning
confidence: 99%